Manajemen Emosi Berbasis Mindfulness Untuk Kesuksesan Bisnis Umkm Perempuan: Program Pelatihan Di Komunitas Rumah Hasanah Bandung - Firdasannah, Astri; Jihan Eka Aulianti; Anggun Zachra Julaiha; Cyndi Fiolanda Hermawan; Asysyifa Fauziah (PUSAKO : Jurnal Pengabdian Psikologi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, contributing over 99% of total business entities and absorbing 97% of the workforce. Female entrepreneurs face unique emotional and social challenges due to multiple roles, business pressures, and limited emotional regulation skills. This community service program aimed to enhance emotional management and mindfulness skills among female MSME entrepreneurs in the Rumah Hasanah Bandung Community. The program was conducted through interactive workshops, mindfulness practices, role plays, and emotional journaling. Evaluation through pre- and post-tests showed an average knowledge improvement of 29%, with a 91.7% satisfaction rate. Participants reported improved emotional awareness, patience, self-confidence, and communication skills. This program demonstrated the effectiveness of emotional management training in improving psychological well-being and sustainable business performance among women entrepreneurs.